SOME PROBLEMS OF ECOLOGICAL GEOMORPHOLOGY OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
Ecological geomorphology is a new scientific direction of geomorphology. According to the authors, the research in this direction should be focused on clarifying the impact of relief and relief-forming processes on human economic activity: and vice versa, how human activity affects the existing relief and relief-forming processes. Ecological geomorphology has great development prospects in Armenia, given the mountainous nature of the relief and the prevalence of a number of dangerous exogenous processes. Among the urgent problems in Armenia are: identification of safe construction sites, study of the stability of mountain slopes for their engineering development, study of the relief in the exploration and development of mineral deposits, the use of hollow relief forms for storing dumps for mining. In terms of dangerous exogenous relief-forming processes, the landslides and debris flows have the greatest negative impact on the environmental situation in Armenia. Stonefalls and snow avalanches have a local distribution and do not cause much harm to the environment of the republic. It is noted that it is necessary to prepare a map of ecological and geomorphological zoning (based on a general geomorphological map), which should show the areas of ecological and geomorphological risk and the areas with urgent environmental problems. At the first stage, such zoning can be performed at a scale of 1:500,000, and at a larger scale for specific development sites. In connection with the activation of landslides in the most active landslide areas, it is proposed to carry out drainage works to prevent further destructive processes at the first stage of anti-landslide measures. Regarding mudflows, as priority preventive measures it can be recommended to clean and deepen the channels of all watercourses, as well as to clean the bridge passages in order to prevent the flow masses from leaving the watercourses, as well as to avoid the formation of congestion in front of bridges. In the future, terracing of slopes and the construction of barrages on active flow watercourses are desirable.
Keywords: Armenia; debris flow; ecological geomorphology; landslide; problem